Dinâmica do uso e ocupação do solo e aplicação de índices de vegetação em uma sub-bacia hidrográfica do Rio Acará, no município de Tomé-Açú, Pará, entre os anos 1995 e 2017 - SILVA, Laiane Pinto da (2020)
Remote sensing images have been used as data sources for geological, environmental, agricultural, cartographic, forestry, urban, oceanographic studies and surveys, among others. Land use and occupation is related to socioeconomic factors and causes changes in natural factors, which transform and, when mismanaged, cause various negative impacts such as erosion, flooding, flooding, drought, housing loss, death, among others, directly and indirectly affecting social factors. To mitigate these problems and foster the development of public policies for sustainable management of natural resources, it is essential to monitor land use and land cover through detailed temporal and spatial information on changes in the landscape. Given the above, the objective of this work was to perform a spatiotemporal analysis and identify the dynamics of land use and vegetation cover in a sub-basin of the Acará river, located in northeastern Pará. The software used in this work was Arcgis® 10.5.1 and eCognition Developer 64 9.0®. Land use and occupation maps and vegetation indices (NDVI, SAVI and IAF) were generated for the years 1995, 2008 and 2017. The main changes in the sub-basin occurred in the forest, exposed soil and cultivated area classes, with forest areas decreasing (from 54.5% to 38.5%), and increased areas of exposed soil (from 11.7%). to 23.9%) and a considerable increase in cultivated areas between 1995 and 2008 (from 13.6% to 25.9%) with consecutive reduction between 2008 and 2017 (from 25.9% to 17.5%). It was concluded that urban occupation had a great influence on the alterations suffered in the subwatershed area. from the Acará river. Thematic maps of the processed images with Normalized Difference Vegetation Index (NDVI), Soil Adjusted Vegetation Index (SAVI) and Leaf Area Index (IAF) achieved good performance for analysis of land use and land cover in the watershed. from the Acará river. The adoption of agroforestry systems (SAFs) based on agroecological practices is recommended as an alternative to monoculture in the region.